2020
DOI: 10.3892/ijmm.2020.4541
|View full text |Cite
|
Sign up to set email alerts
|

Association between oxidative stress biomarkers and PON and GST polymorphisms as a predictor for susceptibility to the effects of pesticides

Abstract: Low levels of pesticides persist in the environment and can affect the health of exposed subjects. Oxidative stress is considered as one of the mechanisms responsible for the adverse effects on human health and some molecules may represent useful biomarkers for the evaluation of this physiological balance. This study investigated the role of these biomarkers, such as advanced oxidation protein products (AOPP), advanced glycation end-products (AGE) and reactive oxygen metabolites (ROMs) in relation to genetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…Many efforts, focusing on the mechanisms of oxidative stress and the role played by the genetic profile in terms of susceptibility, have been conducted [ 14 , 15 , 16 ]. Recently, different studies have demonstrated that gut microbiota (GM) can be affected and altered by different types of environmental pollutants, including some pesticides [ 17 ], therefore the role of the gut microbiota in pesticide-induced toxicity in non-target organisms is gaining increasing attention [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts, focusing on the mechanisms of oxidative stress and the role played by the genetic profile in terms of susceptibility, have been conducted [ 14 , 15 , 16 ]. Recently, different studies have demonstrated that gut microbiota (GM) can be affected and altered by different types of environmental pollutants, including some pesticides [ 17 ], therefore the role of the gut microbiota in pesticide-induced toxicity in non-target organisms is gaining increasing attention [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that more than half of species living in the central human GM are sensitive to Gly (84). In addition to altering the microbial composition, a possible mechanism of action could be the modification of microRNAs (miRNAs) expression and immunomodulation as suggested by several studies (85)(86)(87). The mRNA expression levels of several inflammatory mediators [Nuclear factor kappa B (NF-κB), Tumour necrosis factor α (TNF-α), Caspase-3, MAPK3, IL-1β, and IL-6] resulted in increase after exposure to Gly, highlighting a notable decrease in the abundance of Firmicutes and enhancement of pathogenic bacteria (60,61).…”
Section: Pesticidesmentioning
confidence: 99%
“…Genetic polymorphism refers to the presence of two or more alleles, at a particular locus. Depending on the allele and the gene, these polymorphisms may either protect the individual from pesticides-induced oxidative damage, or conversely, makes its more vulnerable ( 55 , 56 ). For example, two important polymorphisms (Q192R and L55M) in the human paraoxonase 1 (PON1) gene, a hydrolytic enzyme, which protects the toxicity of organophosphates insecticides, have opposing roles.…”
Section: Analysis Of Epidemiological Differencesmentioning
confidence: 99%